THE BENEFITS OF SIGN LANGUAGE FOR DEAF CHILDREN WITH AND WITHOUT COCHLEAR IMPLANT(S) - Klaudia, Krammer (European Scientific Journal, ESJ, 2014)
Prelingual deaf children do not have sufficient access to sound to be able to acquire a spoken language via the acoustic channel. The same is true of many deaf children who received one or two cochlear implants: Only a small segment of these children profit from the implant(s) in such a way that they can acquire spoken language naturally. For most children the implants are improving the access to sound but not sufficiently to be able to reach a normal language competence. In order to give these children the possibility to develop a functioning communication system and to guarantee normal development they need a language which is totally accessible to them - a sign language. The consequences of language deprivation for the development of a child are known from developmental psychology. To avoid this, sign language from the very beginning offers a deaf child the possibility to communicate at any stage in life and guarantees thus a normal development. Using a sign language does not mean the exclusion of a spoken language and vice versa; the use of a sign language and the development of spoken/written language should happen in parallel. What is crucial is that each child should have the possibility to communicate according to its needs and thus has the chance of a normal development.